Clinico-bacteriological study of vesical calculus: a prospective study - Tekam, Vijay Kumar; Choube, Abhishek (International Surgery Journal, 2017)
Background: The incidence of primary bladder calculi in developed countries has been steadily and significantly declining since the 19th century because of improved diet, nutrition and infection control. In these countries, vesical calculi affect adults. However, bladder calculi remain common in developing and less developed countries. Despite the presence of several studies in countries with a high incidence of the disease, no complete uniformity in the reporting of data exists. Methods: The present study was carried out in 76% admitted patient of vesical calculus, investigated and treated by spcl. Some stones were subjected to bacteriological culture. Results: Incidence of vesical calculus was 1.01% of the total surgical admission and 14.87% out of total genito-urinary disease cases.Maximum number of patients were in the age group 0-10 years. Males predominated the females with a 12:1 ratio. E.coli was the commonest organism covering 22.3% of infection. All the cases were managed by spcl. Conclusions: It was concluded from our study that were common in children with low socio-economic status. Metabolic, infective, stasis and vitamin a deficiency (MISA) remained the important factor in its formation. They are usually single and commonly of mixed variety.